Palmar triaxial force magnitudes as predictors of sprint front crawl performance - Simoes, J.; Bottom, M.; Haworth, J. (Sports Biomechanics, 2026)
The development of wearable technology in swimming has enabled easier collection of greatly detailed stroke metrics across researchers and practitioners alike. In particular, the use of pressure sensors on swimmers` palms allows for a nuanced analysis of the stroke cycle previously only available via time-intensive video analysis. This study aimed to evaluate whether triaxial force magnitudes recorded via wearable sensors could predict sprint swimming performance. Twenty-five NCAA Division I swimmers (13 female, 12 male; age 20.5 ± 1.6 years) participated in three maximal-effort 50-metre front crawl swims. Force data were summarised into three directional magnitudes—propulsive, vertical, and lateral. Multiple regression analysis indicated that greater propulsive (p = 0.03) and downward (p = 0.01) force on the left hand were significantly associated with faster swim times (R2 = 0.38, p < 0.01), whereas right-hand forces were not significant predictors of performance (p = 0.05). These findings suggest that swimmers and coaches may benefit from emphasising propulsive and downward force production during sprint front crawl. Further research is needed to understand how the asymmetries between hands, particularly relating to hand dominance and breathing preference, affect propulsion.